2003
DOI: 10.1002/sce.10101
|View full text |Cite
|
Sign up to set email alerts
|

The morality of socioscientific issues: Construal and resolution of genetic engineering dilemmas

Abstract: ABSTRACT:The ability to negotiate and resolve socioscientific issues has been posited as integral components of scientific literacy. Although philosophers and science educators have argued that socioscientific issues inherently involve moral and ethical considerations, the ultimate arbiters of morality are individual decision-makers. This study explored the extent to which college students construe genetic engineering issues as moral problems. Twenty college students participated in interviews designed to elic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
218
2
47

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 364 publications
(280 citation statements)
references
References 46 publications
13
218
2
47
Order By: Relevance
“…As shown by other studies, a variety of norms is expected to be found among students (Sadler & Zeidler, 2004). When the students participating in our study used norms to legitimize their signification of gene technology, they focussed attention on a variety of interesting norms that uncovered potential latent conflicts for science classroom discussions.…”
Section: Discussion Of Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…As shown by other studies, a variety of norms is expected to be found among students (Sadler & Zeidler, 2004). When the students participating in our study used norms to legitimize their signification of gene technology, they focussed attention on a variety of interesting norms that uncovered potential latent conflicts for science classroom discussions.…”
Section: Discussion Of Resultsmentioning
confidence: 71%
“…The validity of this study is further strengthened by the presence of similar arguments about gene technology in other studies. For example, see Bates, Lynch, Bevan, and Condit (2005), Barnett, Cooper, and Senior (2007), Chen and Raffan (1999), Gunter et al (1998), Kolstø et al (2006), Pearce, Thomas, and Clements (2006), Saucier and Cain (2006), Sadler and Donnelly, (2006) Sadler and Zeidler (2004), Walker and Zeidler (2007), Zeidler, Walker, Ackett, and Simmons (2002), and Zohar and Nemet (2002).…”
Section: Discussion Of Methodologymentioning
confidence: 99%
“…SSIs have been included in many carefully designed teaching interventions (see, for example, Albe, 2008;Sadler & Zeidler, 2004;Tomas, Ritchie, & Tones, 2011;Walker & Zeidler, 2007;Zohar & Nemet, 2002). They have also been included in science courses that receive a recognised qualification, such as the Dutch ANW (Public Understanding of Science) course (which in 1999 was compulsory for all 15 -19-year-olds, see Eijkelhof & Kapteijn, 2000) and, in England, in specific post-16 (and non-compulsory) biology and chemistry courses (Hughes, 2000;Lewis & Scott, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Such issues are typically defined as issues that on the one hand have a conceptual basis in science, and on the other hand arise as issues within the ethical, political, and economical realm of society (e.g. Sadler & Zeidler, 2003). In contrast, we will use the slightly awkward term THE ROLE OF SOCIOSCIENTIFIC ISSUES 'socioscientific teaching activities' to denote the teaching situations or activities in which one or more specific socioscientific issues are thematised -e.g.…”
Section: Introductionmentioning
confidence: 99%